PELATIHAN APLIKASI BELAJAR.ID BERBASIS INTERAKTIF CLASS UNTUK MENGUATKAN KARAKTER MANDIRI SISWA DALAM PEMBELAJARAN DARING DI MASA PPKM - Tirtoni, Feri; Rugaya M; Ika Ratna (Universitas PGRI Adi Buana Surabaya, 2022)
This community service activity aims to overcome the problem of lack of understanding and information from the school community on the development of information technology, especially the e-learning platform that has been provided by the government. Where education itself has many functions, one of which is to familiarize students to become good individuals and have character. In order to be educated optimally, students must do good habits. Since 2020 the Ministry of Education and Culture (Kemendikbud) has launched a strengthening character education (PPK) movement. This movement was initiated by the government with the aim that today's young generation is not only educated academically but also morally educated. With this, students will get used to doing good habits through strengthening the character education provided by the teacher. Independence is a part of life that definitely must be attached in times like this. In addition, independence is also very influential on children's lives in the future when they are adults. These characters will make children ready to face life because armed with independence from a young age, one of the things that can be done is by training the use of the Belajar.id application to train the independence character of students at SDN Sidomulyo 1.